2010
DOI: 10.1038/onc.2010.226
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a molecular recognition feature in the E1A oncoprotein that binds the SUMO conjugase UBC9 and likely interferes with polySUMOylation

Abstract: Hub proteins have central roles in regulating cellular processes. By targeting a single cellular hub, a viral oncogene may gain control over an entire module in the cellular interaction network that is potentially comprised of hundreds of proteins. The adenovirus E1A oncoprotein is a viral hub that interacts with many cellular hub proteins by short linear motifs/molecular recognition features (MoRFs). These interactions transform the architecture of the cellular protein interaction network and virtually reprog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…DREF was detected using a polyclonal anti-DREF antibody, GST was detected using a polyclonal anti-GST antibody, and input E1A was detected using the M73 antibody. E1A was previously found to alter the number and size of PML bodies in infected cells, we suspected that DREF was colocalized with PML bodies (31,33). Furthermore, SUMOylation is a key feature of many PML-associated proteins, and we observed altered SUMOylation of DREF (Fig.…”
Section: R (13s)supporting
confidence: 56%
See 3 more Smart Citations
“…DREF was detected using a polyclonal anti-DREF antibody, GST was detected using a polyclonal anti-GST antibody, and input E1A was detected using the M73 antibody. E1A was previously found to alter the number and size of PML bodies in infected cells, we suspected that DREF was colocalized with PML bodies (31,33). Furthermore, SUMOylation is a key feature of many PML-associated proteins, and we observed altered SUMOylation of DREF (Fig.…”
Section: R (13s)supporting
confidence: 56%
“…E1A was previously reported to interact with UBC9, a SUMO conjugase (31,32). Interaction of E1A with UBC9 is required for alteration of PML body morphology in E1A-expressing cells (31), and this is abolished by the loss of E1A binding to UBC9 by the E1A T123H mutant.…”
Section: R (13s)mentioning
confidence: 97%
See 2 more Smart Citations
“…It has previously been shown that the viral early protein E1A represses SUMO modification of the retinoblastoma protein and interacts with the SUMO-conjugating enzyme Ubc9 to likely interfere with polySUMOylation (76,77). Therefore, we tested if E1A triggers reduced SUMO-2 modification of Sp100 (Fig.…”
Section: Sp100 Depletion Promotes Ad Progeny Production and Early Virmentioning
confidence: 99%